Hospital Budget Increase for Information Technology During Phase 1 Meaningful Use. Issue 2 (April 2015) - Neumeier, Harold; Berner, Eta S.; Burke, Darrell E.; Azuero, Andres
<x xml:space="preserve">Abstract</x> Federal policies have a significant effect on how businesses spend money. The 2009 HITECH (Health Information Technology for Economic and Clinical Health Act) authorized incentive payments through Medicare and Medicaid to clinicians and hospitals when they use certified electronic health records privately and securely to achieve specified improvements in care delivery. Federal incentive payments were offered in 2011 for hospitals that had satisfied "meaningful use" criteria. A longitudinal study of nonfederal hospital information technology (IT) budgets (N = 493) during the years 2009 to 2011 found increases in the percentage of hospital annual operating budgets allocated to IT in the years leading up to these federal incentives. This increase was most pronounced among hospitals receiving high proportions of their reimbursements from Medicaid, followed by hospitals receiving high proportions of their reimbursements from Medicare, possibly indicating a budget shift during this period to more IT spending to achieve meaningful-use policy guidelines.